Pengenalan Strategi Digital Branding Untuk Meningkatkan Penjualan Umkm Pada Komunitas Umkm Desa Gelam Jaya, Kabupaten Tangerang - Santosa, Sonny; Novianti, Rini; Angreni, Tri; Elizabeth, Elizabeth; Tholok, Fidellis Wato; Herijawati, Etty; Gustriandi, Andre (LP3kM Universitas Buddhi Dharma, 2021)
This is the time for us to see the positive side caused by pandemic. Even though not everybody agrees to this, the pandemic going on not only in Indonesia but also in all over the world has given us a chance for ‘adaptation’ over changes in business. Nowadays, business concept is not only affected by markets, companies, competitors but also by changes. Every individual, even a big company must acknowledge this. In order to maintain the side of people’s ‘economy’, various studies reviewing alternatives for good marketing strategies have been carried out. These studies are especially aimed at Small and Medium Enterprises (SMEs). This is because SMEs have been the part of creative economy. Based on these circumstances, the researcher was encouraged to study which strategy of digital branding dominantly carried out by the SME players. This research applied factor analysis to find out the basic attribute grounding SME players to survive their businesses, which were initiated either before or after pandemic. The method used was non-probability sampling. Here the questionnaires were distributed in order to find answers from five determined spots. There were 169 respondents as samples in this research. In the pre-test, before questionnaires distributed, there were at least 9 attributes used as references for the main players of SMEs in applying digital branding. Results of factor analysis test showed that there were at least two main factors developed. In these two factors, it is agreed that strategy of Search Engine Optimization was the most ideal to apply in order to survive their business. This is because it has big dominant value, which was 0.823 (82% for first group) and 0.790 (79% for the second group).